Effect of Engine Rotation on Mechanical Water Pump and Microcontroller-Based Electric Water Pump for Liquid-Cooled Motor Engine on Coolant Temperature - Nike Nur Farida; Muhammad Sidqi Rozin Rabbani; Nicko Nur R (Institute of Research and Community Outreach, Petra Christian University, 2025)
A liquid-cooled motor's cooling system is essential in maintaining engine performance. This study compares mechanical and electric water pumps based on microcontrollers to improve cooling efficiency. This study aims to measure the influence of the two types of pumps on engine temperature. This study uses an experimental method, installing the two types on machines with liquid cooling systems. In this study, thermostat components are also used. Measurements are made on the temperature of the coolant at various engine revolutions (RPM). The results showed that the electric water pump significantly affected the temperature of the coolant. At the coolant temperature, the electric water pump with thermostat obtains the highest coolant temperature at 4500 RPM engine speed of 80.6°C, while the mechanical water pump is 84.25°C. In the thermostat-less test, the electric water pump obtained the highest temperature and coolant discharge of 62.75°C, while the mechanical water pump achieved a temperature of 64.88°C.